Risk Perception, Media, and Ordinary People’s Intention to Engage in Self-Protective Behaviors in the Early Stage of COVID-19 Pandemic in China - Xu T; Wu X (Risk Management and Healthcare Policy, 2022)
Tao Xu, Xiaoqin Wu College of Law and Political Science, Zhejiang Normal University, Jinhua, 321004, People’s Republic of ChinaCorrespondence: Tao Xu, College of Law and Political Science, Zhejiang Normal University, Jinhua, 321004, People’s Republic of China, Email xutao@zjnu.edu.cnObjective: This study aims to examine how risk perception is associated with engagement in preventative behaviors and testing during the COVID-19 pandemic in the early stage of the COVID-19 pandemic in China.Methods: A cross-sectional survey was conducted in February 2020, eventually obtaining 1613 participants, participants’risk perceptions, demographics (sex, age, education level, marital status, and employment status), as well as their engagement in self-protective behaviors and testing were assessed.Results: Risk perception significantly affected intention to engage in self-protective behaviors, the more risk people feel, the more likely they intend to take self-protective actions(β =0.0423; P < 0.01), and simultaneously, people obtaining information on COVID-19 from Official microblogs and public accounts(OMPA) (β =0.189; P < 0.01)and Online websites(OW) (β =0.143; P < 0.1)were more inclined to take self-protective behaviors during the COVID-19 pandemic. It also showed that the interaction of risk perception and Online websites negatively affected the intention to engage in self-protective behaviors(β = − 0.0374; P < 0.05), and conversely, the interaction of risk perception and Overseas media(OM) positively affected self-protective intention(β = 0.0423; P < 0.1).Conclusion: There was a close relationship between the risk perception and the intention to engage in self-protective behaviors. At the same time, the use of media not only directly affected the intention to engage in self-protective behaviors but also moderated the impact of risk perception on the self-protection intention. Specifically, official media directly strengthened the intention to engage in self-protective behaviors. Online websites not only directly affected self-protection intention but also moderated the effect of risk perception on it. Although overseas media had no direct effect on self-protection intention, they moderated the effect of risk perception on it. These conclusions have policy implications for governments’ response to the COVID-19 epidemic.Keywords: risk perception, media, intention to engage in self-protective behaviors, COCID-19 pandemic, self-protective behaviors